2018
DOI: 10.1016/j.ebiom.2018.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of STAT3 signaling promotes cellular reprogramming into insulin-producing cells induced by defined transcription factors

Abstract: BackgroundSTAT3 has been demonstrated to play a role in maintaining cellular identities in the pancreas, whereas an activating STAT3 mutation has been linked to impaired β-cell function.MethodsThe role of STAT3 in β-cell neogenesis, induced by the exogenous expression of Pdx1, Neurog3, and Mafa, was analyzed in vitro and in vivo.FindingsThe expression of phosphorylated STAT3 (pSTAT3) was induced in both Pdx1-expressing and Mafa-expressing cells, but most of the induced β cells were negative for pSTAT3. The sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
2
12
1
Order By: Relevance
“…STAT3 signalling has been demonstrated to be essential for human pancreas development and endocrine differentiation (17). We observed almost complete STAT3 inactivation in the first stages of stem cells reprogrammed into β-like cells, in line with published data (64). STAT3 is a target of PDX1 (51), binds to the Neurog3 promoter (65) and is involved in the activation of NEUROG3 in differentiating human embryonic stem cells (66).…”
Section: Discussionsupporting
confidence: 89%
“…STAT3 signalling has been demonstrated to be essential for human pancreas development and endocrine differentiation (17). We observed almost complete STAT3 inactivation in the first stages of stem cells reprogrammed into β-like cells, in line with published data (64). STAT3 is a target of PDX1 (51), binds to the Neurog3 promoter (65) and is involved in the activation of NEUROG3 in differentiating human embryonic stem cells (66).…”
Section: Discussionsupporting
confidence: 89%
“…16 Signal transducer and activator of transcription (STAT3) has been proved to be involved in cell differentiation of the nervous system. 17 The STAT3 signaling pathway has been identified as a critical participant in neuroinflammation, and its activation has been found in the spinal dorsal horn of both spinal cord injury and neuropathic pain models. 18 The current study has shown that miR-7a could affect neuropathic pain development via the STAT3 signaling pathway by regulating NEFL based on the rat model of SNL, which offers a better understanding for the underlying molecular mechanisms in neuropathic pain progression.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 has a role in cell differentiation in various systems including immune and endocrine systems. However recent studies showed that STAT3 suppression together with Pdx1 expression increased the number of β-cells ( Miura et al, 2018 ). Caffeic acid (TP15), t -ferulic acid (TP18), 4α-[(β-D-glucopyranosyloxy)methyl]-5α-(2-hydroxyethyl)-3-methylcyclopent-2-en-1-one (TP22), 5α-[2-(β-D-glucopyranosyloxy)ethyl]-4α-hydroxymethyl-3-methylcyclopent-2-en-1-one (TP23), and teupolin VIII (TP29) showed interaction with the target STAT3 ( Table S5 ).…”
Section: Discussionmentioning
confidence: 99%